GIVING VOICE TO OUR CORE FRENCH STUDENTS: IMPLICATIONS FOR ATTRITION AND THE DISCOURSE ON THE BENEFITS OF LEARNING FSL IN ONTARIO - Arnott, Stephanie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2019)
This article explores student motivation to learn French as a second language (FSL) in school. Ontario Grade 9 students (N = 63) were surveyed on their intention to (dis)continue studying French in the Core French (CF) program in Grade 10 when FSL becomes optional. Survey participants shared their reasoning, and a subset (n = 7) took part in a focus group. Although motivating factors to (dis)continue in CF align with previous studies, participants openly contemplated the relevance of these factors to their lives. In response, this article explores the discourse on the benefits of learning French and debates its applicability to adolescent FSL learners. The implications for efforts to address CF attrition and promote FSL learning are also discussed.